2018
DOI: 10.12820/rbafs.v.22n6p512-22
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do treinamento intervalado de alta intensidade versus treinamento contínuo na composição corporal: uma revisão sistemática com meta-análise

Abstract: A Obesidade é um fator de risco para doenças cardiovasculares e a sua prevalência cresce a cada ano atingindo mais de 2 bilhões de adultos no mundo. As principais recomendações para perda de gordura concentram-se em exercícios de estados estacionários de intensidades moderadas. Entretanto, essas diretrizes não conseguem ser atendidas pela maior parte da população adulta. Sendo assim, novas modalidades ou intensidades de exercícios vem sendo propostas na tentativa de promover perdas mais si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
8
0
1
Order By: Relevance
“…The study of Keating et al, published at 2014, also is utilized in several meta-analyses 5,6,8 and has a high score on the TESTEX scale of methodological quality. However, analyzing this intervention of 12 weeks, we observed that in the four initial weeks (2/3 of intervention), the participants performed four to six sprints of 30-45s on 120% of V̇O2peak, with 120-180s of active recovery periods at 30W.…”
Section: Methodology Of Interventionsmentioning
confidence: 99%
See 4 more Smart Citations
“…The study of Keating et al, published at 2014, also is utilized in several meta-analyses 5,6,8 and has a high score on the TESTEX scale of methodological quality. However, analyzing this intervention of 12 weeks, we observed that in the four initial weeks (2/3 of intervention), the participants performed four to six sprints of 30-45s on 120% of V̇O2peak, with 120-180s of active recovery periods at 30W.…”
Section: Methodology Of Interventionsmentioning
confidence: 99%
“…Regarding HIIT prescription, Fisher et al study, published at 2015, are also included in some meta-analysis 5,6,8 and have some issues. This study was conducted to investigate possible differences between models of aerobic exercise, considering the hypothesis that higher volume in MICT would lead to better outcomes.…”
Section: Methodology Of Interventionsmentioning
confidence: 99%
See 3 more Smart Citations